2007
DOI: 10.1111/j.1600-0765.2006.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Defense mechanism of heme oxygenase‐1 against cytotoxic and receptor activator of nuclear factor‐κB ligand inducing effects of hydrogen peroxide in human periodontal ligament cells

Abstract: These data suggest that heme oxygenase-1 induction plays a protective role in periodontal ligament cells against the cytotoxic and RANKL-inducing effects of H2O2, through multiple signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
3
29
0
1
Order By: Relevance
“…[19][20][21][22][23][24] In the present study, we found that MS increased HO-1 mRNA and protein expression in PDLCs. These findings are consistent with our previous study in which osteogenic differentiation Figure 4.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[19][20][21][22][23][24] In the present study, we found that MS increased HO-1 mRNA and protein expression in PDLCs. These findings are consistent with our previous study in which osteogenic differentiation Figure 4.…”
Section: Discussionsupporting
confidence: 66%
“…21,22,24 Increases in the expression of HO-1, BMP-2, BMP-7, and Runx-2 resulting from treatment with LPS and MS were attenuated by preincubation with selective inhibitors of p38, ERK, PI3K, PKG, and NF-kB (SB203580, U0126, LY294002, KT5823, and PDTC, respectively). These results suggest that LPS-induced and MS-induced HO-1 and BMP expression occurs via the activation of p38, ERK MAPK, PI3K, PKG, and NF-kB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported previously that proinflammatory cytokines [30] and nitric oxide [31] induced expression of HO-1, which potentially plays a role in cytoprotection within human pulp cells. Moreover, induction of HO-1 plays a protective role in PDL cells by combating H2O2 through multiple signalling pathways [32]. HO-1 countering the inductive effects of CCL20 in PDL cells has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…14) One of three mammalian HO isoforms, HO-1 (also called heat shock protein 32), is a stress-responsive protein induced by various agents and is involved in a variety of regulatory and protective mechanisms in cells. 15,16) We previously reported that HO-1 is induced by pro-inflammatory cytokines, NO, substance P, hydrogen peroxide, and mechanical stress, [17][18][19][20][21][22][23] and that it may play a cytoprotective role in human pulp and PDL cells. However, HO-1-mediated NOinductive effects of osteoblastic differentiation in PDL cells has not yet been reported.…”
mentioning
confidence: 99%